ECOLOGICAL CHARACTERISTICS OF SOILS AND VEGETABLES OF GARDENS LOCATED IN THE INDUSTRIAL AREA AND OUTSIDE THE CITY OF UST-KAMENOGORSK (Eurasian Journal of Ecology, 2024)
In this study, ecological evaluation of the soils of the gardens located in the industrial area and in the suburbs was given. The results of physical and chemical analysis of soil samples were summarized, and the obtained data were statistically processed. Soil and vegetable samples for analysis were taken from private gardens located in the city near «Kazzinc» LLC. In addition, samples were collected from the outskirts of the city - Akhmirova village for comparative analysis. These samples were prepared for chemical analysis and the content of Zn, Pb, Cu and Cd was determined.It was found that the amount of heavy metals analyzed in the soils of the studied areas is several times higher in the industrial area than in the suburban area. The average values of the analyzed metals in the industrial soils of all studied regions are higher than the safe level accepted in Kazakhstan. In the samples taken in the industrial area, the content of all investigated heavy metals was 2 to 8 times higher than the internationally recommended safe level. Despite being grown in the same environmental conditions, vegetables have different accumulation levels of heavy metals. However, it should be noted that the high concentration of heavy metals in the soil has an effect on their content of the plant. The highest amount of heavy metals was found in vegetables grown in the industrial area, and the lowest in the suburban area.